PELAYANAN KEPENDETAAN DAN KEAKTIFAN JEMAAT DALAM PERIBADATAN - Alan Hubert Frederick Sanger; Frans Sanger; Juwinner Dedy Kasingku; Yornal Buladja (Nusantara Hasana Journal, 2022)
This study attempts to determine the level of the pastor's ministry, the level of the congregation's participation in worship, and whether there is a significant relationship between the pastor's ministry and the congregation's involvement in worship. The instrument used is a questionnaire for the pastor's ministry that was modified from Wentuk (2013), and a "self-made" questionnaire for the congregation's participation in worship. The study involved 100 church members from Gethsemane, Danuwudu, Orion, and Lembah Doa, and data was collected using a convenience sampling method. This study revealed that a pastor's ministry was within the high category. As a result, church services are frequently attended by the Gethsemane, Danuwudu, Orion, and Lembah Doa congregations. Additionally, there is a strong connection between the congregation's participation in worship and the pastor's ministry. It suggests that church members will participate actively in church services if the pastor invests a lot of time in the areas of pastoral care, preaching, and evangelism.